Methodological challenges and biases in the field of cognitive function among patients with chronic kidney disease - Giannakou, Konstantinos; Golenia, Aleksandra; Liabeuf, Sophie; Malyszko, Jolanta; Mattace-Raso, Francesco; Farinha, Ana; Spasovski, Goce; Hafez, Gaye; Wiecek, Andrzej; Capolongo, Giovanna; Capasso, Giovambattista; Massy, Ziad A.; et al. (Frontiers in Medicine, 2023)
Chronic kidney disease (CKD) affects approximately 850 million people globally and is associated with an increased risk of cognitive impairment. The prevalence of cognitive impairment among CKD patients ranges from 30% to 60%, and the link between CKD and cognitive impairment is partially understood. Methodological challenges and biases in studying cognitive function in CKD patients need to be addressed to improve diagnosis, treatment, and management of cognitive impairment in this population. Here, we review the methodological challenges and study design issues, including observational studies' limitations, internal validity, and different types of bias that can impact the validity of research findings. Understanding the unique challenges and biases associated with studying cognitive function in CKD patients can help to identify potential sources of error and improve the quality of future research, leading to more accurate diagnoses and better treatment plans for CKD patients.